Multi-scale CT imaging technique characterization of volcanic rock reservoirs: a study case from the Changling fault depression of the southern Songliao Basin - Zhu, Jianfeng; Liu, Yuhu; Hu, Zhiwei (Frontiers in Earth Science, 2025)
The Changling fault depression in the southern Songliao Basin hosts volcanic rock reservoirs with significant oil and gas potential, yet their complex pore structures require advanced characterization to optimize resource exploration. To address this, we employed multi-scale computed tomography (CT) imaging combined with mercury intrusion porosimetry (MIP) to analyze three representative volcanic rock samples through three-tier micrometer CT scanning. This integrated approach enabled the construction of a multi-scale digital rock model, facilitating qualitative and quantitative evaluations of pore-throat structures across diverse storage spaces. Results revealed detailed three-dimensional distributions of porosity, connectivity, and pore-throat radii, demonstrating pronounced heterogeneity in reservoir properties. The results demonstrate that integrating multi-scale CT scanning with mercury intrusion data provides a robust method for characterizing the three-dimensional pore distribution effectively. This research provides an in-depth understanding of the microscopic characteristics of volcanic rock reservoirs and establishes a scientific and technical foundation for advancing the exploration and development of oil and gas resources.